Perlindungan Buruh Migran Indonesia di Korea Selatan di Masa Pandemi Covid-19: Protection of Indonesian Migrant Workers in South Korea during the Covid-19 Pandemic - Sulistiyono, Tri; Arifin, Ridwan; Wedhatami, Bayangsari; Damayanti, Ratih (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
The number of Indonesian migrant workers placed in South Korea in recent years has tended to increase. In 2018 there were 6,921 workers placed in South Korea in various sectors. This number increased from the previous year which only 3,719 people. The placement scheme is carried out through a Government to Government (G to G) cooperation scheme between the two countries through the National Agency for Placement and Protection of Indonesian Workers (BNP2TKI) and South Korea’s Employment Permit System (EPS). The study intends to examine, analyze, and explore more about the policy of placing Indonesian workers in South Korea as well as various legal protections provided by the South Korean government. This research is a collaborative research initiated through the G-to-G program by the Faculty of Law, Universitas Negeri Semarang, and the South Korean government. This research involved the Study Center and Labor Law Clinic of the Faculty of Law of UNNES, the Center for Legal Drafting, Policy and Development at the Faculty of Law of UNNES, Hankuk University of Foreign Studies Hankuk College of Law, and Law Research Institute Hankuk University of Foreign Studies. This research is empirical legal research, where the research was carried out in two countries: Indonesia and South Korea. The purposes of the research are to: (1) to investigate the effectiveness of national and international law instrument on the protection to migrant workers in South Korea, (2) to identify the specific policies on South Korea for Southeast foreign workers as well as Indonesian migrant workers, and (3) to analyze the cooperation both South Korea and Indonesia on sending migrant workers. The research will be carried out for eight months in two countries. Research in Indonesia will be focused on Jakarta (in several labor related institutions), while in South Korea it will focus on the Hankuk University of Foreign Studies, the Indonesian Embassy in South Korea, the Association of Indonesian Workers in South Korea, the South Korean Student Association of Indonesia (Perpika), and Human Resources Development Service of Korea.